In Vitro Antibacterial Activity of a Combination of Stingless Bee Propolis and Premna corymbosa Leaves Extract Against Streptococcus mutans: Aktivitas Antibakteri In Vitro Kombinasi Propolis Lebah Kelulut Dan Ekstrak Daun Premna corymbosa Terhadap Streptococcus mutans - Rizki Ramdani; Tiara Halidah Ratnasari; Paula Mariana Kustiawan; Harlinda Kuspradini (Universitas Muhammadiyah Sidoarjo, 2026)
Dental caries remains a major oral health problem primarily caused by Streptococcus mutans, and natural products such as stingless bee propolis and Premna corymbosa leaves have potential antibacterial properties. This study aimed to evaluate the in vitro antibacterial activity of a combination of stingless bee propolis and P. corymbosa leaf extract against S. mutans using the microdilution method. Five formulations were prepared: F1 (100% P. corymbosa), F2 (75:25), F3 (50:50), F4 (25:75), and F5 (100% propolis), with clindamycin and ethanol as positive and negative controls. Antibacterial activity was determined based on optical density values and analyzed using one-way ANOVA. The results showed a dose-dependent antibacterial effect, with the highest inhibition observed in F5 (57.51%), followed by F4 (39.99%) and F3 (26.11%), and statistically significant differences among treatment groups (p < 0.05). Phytochemical screening revealed the presence of flavonoids, saponins, terpenoids, alkaloids, and tannins, which are associated with antibacterial mechanisms. In conclusion, the combination of P. corymbosa leaf extract and stingless bee propolis demonstrated significant in vitro antibacterial activity against S. mutans and shows potential as a natural alternative or complementary agent for oral health applications.